Sensitive Detection and Quantification of Burkholderia pseudomallei in Soil Samples Using Culture-Dependent and-Independent Approaches - Trinh, Thanh Trung (NXB Nông Nghiệp, 2011)
Burkholderia pseudomallei, the causative agent of melioidosis, is a soil-dwelling Gram-negative bacterium. Although the bacterium has been known for a century, its worldwide distribution as well as its natural lifestyle still remains uncertain. Detection of B. pseudomalleiusing culture-dependent and-independent methods has been previously reported. However, these methods have demonstrated either lack sensitivity or inaccurate quantification; therefore, environmental samples containing low numbers of B. pseudomalleiwill likely remain undetected or unquantifiable